Etnomatematika pada Alat Upacara Adat dan Alat Mata Pencaharian Etnis Melayu di Museum Negeri Sumatera Utara: Studi Eksplorasi - Ahmadsyah Fauzian Rambe; Alfito Fatihah; Farizi Aqfi; Siti Zia Hadatul Hasanah; Syifa Husna Ramadhani; Wulan Dari; Ella Andhany (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study examines ethnomathematics in traditional tools of the Malay ethnic group at the North Sumatra Provincial Museum, encompassing ceremonial and livelihood tools. The research employs a qualitative approach using ethnographic methods to explore the mathematical concepts embedded in these objects. Ceremonial tools such as bentan, tiered trays, incense burners, and glass holders were analyzed based on geometric concepts such as circles, cylinders, ratios, and sequences, while livelihood tools such as goat hoofs, horns, sickle, and one-sided fish traps represent spatial geometry, symmetry, and volume concepts. The findings reveal that these traditional objects not only serve practical purposes but also contain mathematical and philosophical values reflecting Malay culture. These tools can be utilized as context-based mathematics learning media, helping students understand mathematics through the lens of local culture. This study emphasizes the significant role of ethnomathematics in integrating education with cultural preservation while strengthening local identity in the era of globalization.